Evaluasi Pelaksanaan Manajemen Terpadu Balita Sakit (MTBS) Di Puskesmas Kota Ratu Kabupaten Ende Tahun 2021 - Dian Arifiyanti Syafitri Rodja (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background : Â In country develop, more from 12 million child in lower age 5 year die due to pneumonia, diarrhea, malaria, measles and malnutrition. Kota Ratu Health Centervarious diseases in toddlers are still found, this requires an evaluation of the implementation of IMCI at the public Health. Purpose from study this is for know implementation IMCI includes input, process, output and outcomein Public health center Kota Ratu Regency Ende Year 2021. Methods: Type study which used study qualitative with approach studies case. The collection of data used is primary data and secondary data.Â Results: Results show that inputs Inadequate facilities and infrastructure at the public health power IMCI which not enough trained. Process implementation IMCI that ischannel service IMCI corresponding with guide book IMCI and officer organize consultation Mother toddler. Output in 2021 have not reached the target, the coverage of services for sick babies and toddlers handled by officers was 72% and the coverage of UCI villages/sub-districts was 50%. Public health Kota Ratu owncasediarrhea highest year 2021 as much 90 toddler.Outcome there were 256 toddlers who visited and 92 toddlers who were sick, the number of visits was caused by COVID-19. Officers and mothers of toddlers were not satisfied with the IMCI services.Conclusion: It is hoped that improvement efforts will be made Public health center like HR, infrastructure, indicatorsachievement who have not met the target, the satisfaction of officers and mothers of toddlers to walk with maximum.